Al-Shafi'i's Perspective on the Method of Resolving the Conflicting Hadiths - Roqiyul Ma’arif Syam (JOURNAL OF QUR'AN AND HADITH STUDIES, 2017)
This article describes the method solution of the maqbul hadith against one another (mukhtalif), which is hadith authenticity or goodwill looks opposite each other authentic hadith or other hadan. However, the meaning of the hadiths it's not the opposite, because with each other on the principle can be solved by: First, compromise trying to collect both, until he lost his match. Second, the goal is to find where between the two hadiths that came first, and where it comes from then. Then the hadith came over first it must be deduced by the hadith who came later. Third, Tarjih is doing research on which powerful hadith neither his nor his eyes, for targeted. A powerful hadith is called a hadith rajih, while the target is called crushed. The solution is according to al-Shafi'i.